RESEARCH RIG FOR EXAMINATION OF PRESSURE IN HYRDODYNAMIC OIL FILM - Wojciech HORAK; Adrian KLUCZNY; Józef SALWIŃSKI (Scientific Journal of Silesian University of Technology. Series Transport)
The paper presents a concept of a didactic research rig for investigation and visualization of pressure distribution in an oil film of a journal fluid friction slide bearing. The rig being presented may be used during classes on subjects associated machine design. The paper presents an idea of a specific design, using an asynchronic motor with a long shaft, on which the slide bearing assembly is fixed. The design is elastic and allows many modifications of the construction. The possible modifications are presented in the summary part of the paper. The paper also presents ideas for development of the design, either to enable measurements of additional physical values, or presentation of specific cases of slide bearings operation.